A EXPERIÊNCIA MÍSTICA APOCALÍPTICA DO APÓSTOLO PAULO COMO ELEMENTO FUNDANTE DA JUSTIFICAÇÃO PELA FÉ: UMA ANÁLISE EXEGÉTICA DE ROMANOS 3 - FORMICKI, LEANDRO (2019)
The purpose of this exegetical study is to search Romans 3:1-31 to see why both the Jew and the Gentile are sinners to the apostle Paul and lack the glory of God (Romans 1:18-3:20). Hence, there is no difference between them in regard to righteousness (3:21-4:25). And because to him the justification of God is by faith in Jesus Christ to all who believe, both Jews and Gentiles, and no longer by the practice of the law (3:22-30). Given this, our hypothesis is to show that from the apocalyptic mystical experience of the Apostle Paul described in Galatians 1:1-24 and 2 Corinthians 12:1-4, he proposes a new interpretation regarding the “salvation of the human being”. This can be confirmed in Romans 3:1-31, where he states that the Torah does not serve as a means of salvation for man, since he is not able to free man from the enslaving power of sin that leads to death. Instead, the means of effective salvation is when “human being is justified by faith, without deeds of the law.” Indeed, this apocalyptic mystical experience takes away the Apostle Paul from the Synagogue Sinaitic Judaism of the Mediterranean World, that is, from a belief in the Sinaitic covenant that is conditioned to the fulfillment of the Torah commandments and considers only the Jewish people as “exclusive of God”, that is , elected to be “holy / separated” and “pure” to God and reallocates him into an apocalyptic mystical space of identity, where he assumes that both Jews and Gentiles are in the condition of “impure” sinners and therefore are not worthy of being justified by God, but by union / communion with the sacred “faith in Jesus” anyone can be considered righteous / innocent / pure and therefore be saved from the wrath of God and receive the reward of one eternal life. To that end, we will base our research on Gershom Scholem, Martinus De Boer and Mary Douglas, respectively on Jewish mysticism, Jewish apocalyptic and cultural anthropology, as well as review some Jewish writings and some exegetical discussions about the text that has been gaining notoriety and controversy since the second half of the twentieth century.